2018
DOI: 10.7759/cureus.2036
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of 8 Gy Single Fraction Palliative Radiation Therapy in Painful Bone Metastases: A Single Institution Experience

Abstract: IntroductionBone metastasis (BM) is a major complication of many solid tumors like breast, prostate, lung and renal cancers. BM leads to serious sequelae of pain, fractures, spinal cord compression and hypercalcemia. Radiotherapy has an established role in relieving pain caused by BM. Worldwide different radiotherapy schedules are being used for BM. The aim of this study is to determine the efficacy of single fraction palliative radiotherapy for painful bone metastases.MethodsBetween April 2014 and April 2017,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…While several randomized single fraction vs. multiple fraction trials have been carried out, the concerns of toxicities and efficacy of the 8 Gy in 1 fraction regimen still remain. Shuja et al and Howell et al described utilization of 3–5 cm margin and <2 cm margin, respectively, from the radiographic involvement for single fraction palliative radiotherapy on conventional c-arm linac modalities (29, 30). The superior bony metastasis visualization combined with improved soft tissue visualization allow for greater precision and enable the utility of a reduced margin in MRgRT of 0.3–0.5 cm as previously demonstrated by Mittauer et al (16).…”
Section: Discussionmentioning
confidence: 99%
“…While several randomized single fraction vs. multiple fraction trials have been carried out, the concerns of toxicities and efficacy of the 8 Gy in 1 fraction regimen still remain. Shuja et al and Howell et al described utilization of 3–5 cm margin and <2 cm margin, respectively, from the radiographic involvement for single fraction palliative radiotherapy on conventional c-arm linac modalities (29, 30). The superior bony metastasis visualization combined with improved soft tissue visualization allow for greater precision and enable the utility of a reduced margin in MRgRT of 0.3–0.5 cm as previously demonstrated by Mittauer et al (16).…”
Section: Discussionmentioning
confidence: 99%
“…The total dosage of cEBRT can vary depending on the size and type of the primary tumor with typical dosages of 25–40 Gy divided into 8–20 fractions [ 96 ]. The standard of care for pain relief in noncomplicated spine metastasis is a single-fraction radiotherapy with a dose of 8 Gy [ 97 , 98 , 99 ]. Single-fraction regimens are cost effective and practical when radiation treatment facilities are limited [ 99 ].…”
Section: Metastasismentioning
confidence: 99%
“…The standard of care for pain relief in noncomplicated spine metastasis is a single-fraction radiotherapy with a dose of 8 Gy [ 97 , 98 , 99 ]. Single-fraction regimens are cost effective and practical when radiation treatment facilities are limited [ 99 ]. However, the benefits of single-fraction radiation need to be weighed with an increased chance of retreatment compared to a multifraction regimen [ 94 ].…”
Section: Metastasismentioning
confidence: 99%
“…However, the optimal radiation dose, fractionation regimen and treatment time remains controversial. Currently, there is increasing interest in resource sparing single fraction of 8 Gy in one fraction for palliating painful spine metastasis [4,5]. Many randomized trials have reported that single fraction of 8 Gy is equivalent to higher radiation doses (20 Gy in 5 fractions or 30 Gy in 10 fractions) [6,7].…”
Section: Introductionmentioning
confidence: 99%